Pengaruh Religiusitas, Literasi, dan Digital Payment Terhadap Kesadaran Melakukan Wakaf Tunai Pada Gen Z - Maulidah Fitrotin, Jihan; Hasanah, Niswatun (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
This research seeks to assess the influence of religiosity, literacy, and digital payment on the awareness of cash waqf among Generation Z, particularly students of Qomaruddin Gresik University. The research employed a quantitative method utilizing primary data collected from 91 participants via purposive sampling. Methods of data collection encompass surveys, literature reviews, and observational studies. Data were examined through classical assumption testing, multiple linear regression, t-tests, and F-tests. The results of the regression analysis indicate that both literacy and digital payment variables positively and significantly influence awareness of cash waqf, whereas religiosity does not have a partial effect. At the same time, the three variables positively and significantly influence cash waqf awareness, exhibiting an F-count value of 33.822 and a significance level of 0.000 (<0.05).The coefficient of determination (R²) value of 0.542 indicates that 54.2% of the variation in cash waqf awareness can be explained by religiosity, literacy, and digital payment variables, while 45.8% is influenced by other factors outside this study. Keywords: Cash Waqf; Religiosity; Literacy; Digital Payment; Generation Z